2019
DOI: 10.3390/cells8060606
|View full text |Cite
|
Sign up to set email alerts
|

C89 Induces Autophagy of Female Germline Stem Cells via Inhibition of the PI3K-Akt Pathway In Vitro

Abstract: Postnatal female germline stem cells (FGSCs) are a type of germline stem cell with self-renewal ability and the capacity of differentiation toward oocyte. The proliferation, differentiation, and apoptosis of FGSCs have been researched in recent years, but autophagy in FGSCs has not been explored. This study investigated the effects of the small-molecule compound 89 (C89) on FGSCs and the underlying molecular mechanism in vitro. Cytometry, Cell Counting Kit-8 (CCK8), and 5-ethynyl-2’-deoxyuridine (EdU) assay sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Many studies have provided convincing evidence that small molecular compounds affect the physiological functions of mammalian cells, such as proliferation, differentiation, autophagy, and apoptosis [13,14,29,45]. In this study, we found that C28 induced significant autophagy, and H3K27ac and ER stress might play roles in C28-induced autophagy of FGSCs in vitro.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Many studies have provided convincing evidence that small molecular compounds affect the physiological functions of mammalian cells, such as proliferation, differentiation, autophagy, and apoptosis [13,14,29,45]. In this study, we found that C28 induced significant autophagy, and H3K27ac and ER stress might play roles in C28-induced autophagy of FGSCs in vitro.…”
Section: Discussionsupporting
confidence: 56%
“…Compound 28 (C28) synthesized from 6-formylbenzoxaborol acts as a Tb LeuRS inhibitor and can be used as a potential novel antitrypanosomal agent. Two benzoxaboroles, C89 and ZCL-082, induce FGSC autophagy in vitro, and the molecular mechanism has been preliminary elucidated [13,29]. However, the epigenetic mechanism of benzoxaborole-induced autophagy of FGSCs and the effects of C28 on FGSCs are largely unknown.…”
mentioning
confidence: 99%
“…Akt, a serine/threonine kinase, is activated by PI3K. It has been reported that PI3K/Akt pathway is engaged in various cellular processes such as apoptosis, inflammatory responses, differentiation, and tumor angiogenesis [46][47][48]. As the upstream gene of NF-κB, Akt could modulate IκB degradation via phosphorylation of IKK in activated BV-2 microglia [49].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the mechanism underlying FGSC self-renewal, differentiation, and autophagy [ 19 , 46 , 51 , 52 ]. Additionally, FGSCs were demonstrated to have the potential to differentiate into oocytes, which provided a new strategy to research oogenesis [ 7 , 41 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing FGSCs and spermatogonial stem cells (SSCs), Li et al uncovered the transcript structures, genetic variants, and interaction between microRNAs and circRNAs [ 20 ]. Li et al suggested that chemical compounds play important roles in modulating FGSCs via the PI3K/Akt pathway [ 19 ]. Additionally, Ma et al revealed that Etv5 , Foxo1 , and Akt genes positively regulate FGSC self-renewal [ 27 ].…”
Section: Introductionmentioning
confidence: 99%